2017
DOI: 10.1108/k-11-2016-0334
|View full text |Cite
|
Sign up to set email alerts
|

Changing perspectives in the face of the decolonisation of knowledge at South African public universities

Abstract: Purpose The legacy of colonisation and apartheid in South Africa has resulted in a radical challenge to the public universities. The successful #FeesMustFall campaign that took place in 2015 accentuated several aspects of post-apartheid transformation that have not been adequately attended to. The public universities are now faced with meeting the needs of students and interested parties who would like to see transformation at various levels, in particular, the decolonisation of knowledge. This paper aims to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…Findings also showed that (71,7%, p = 0,000) of students felt that African traditional legal systems were not recognised in their classrooms and that the exclusion made them feel inferior as African students 61,7% (p = 0,004). These findings are consistent with the views of Baron (2017Baron ( , 1568 who contends that the exclusion of one's culture in a country that is culturally diverse is hurtful, condescending and hostile. The author maintains that a refusal to decolonise the knowledge acquired in South African universities could be described as being prejudicial to African students and the generation of people who were impacted by the segregation of the apartheid educational policies.…”
Section: Discussion Of Findingssupporting
confidence: 90%
See 1 more Smart Citation
“…Findings also showed that (71,7%, p = 0,000) of students felt that African traditional legal systems were not recognised in their classrooms and that the exclusion made them feel inferior as African students 61,7% (p = 0,004). These findings are consistent with the views of Baron (2017Baron ( , 1568 who contends that the exclusion of one's culture in a country that is culturally diverse is hurtful, condescending and hostile. The author maintains that a refusal to decolonise the knowledge acquired in South African universities could be described as being prejudicial to African students and the generation of people who were impacted by the segregation of the apartheid educational policies.…”
Section: Discussion Of Findingssupporting
confidence: 90%
“…Hence, this section of the law curricula is in direct contrast with the lived experiences of African students and as a result becomes alien to students whose parents and other relatives are in relationships according to the dictates of their customs and traditions. According to Baron (2017Baron ( , 1568, the exclusion of one's cultural identity and knowledge in a culturally diverse country such as South Africa is hurtful, condescending and hostile to students. Ramrathan (2016, 5) contends that South African higher education requires deep curricula transformation with a drive to explore and privilege indigenous epistemologies and indigenous knowledge systems.…”
Section: Decolonising the Law Curriculum At The Durban University Of ...mentioning
confidence: 99%
“…There is an underlying critical awareness of the social and political aspects that may be hindering certain groups of people, while also acknowledging the connectedness in the human family. Since a family cannot thrive when some members are suffering (Baron 2017), there is thus a goal to reimagine the world for the upliftment of all. This is enacted by the authentic lecturer who focusses on the students' educational goals (Pask 1976a), even if these goals may initially seem off the topic (earthing a shack).…”
Section: Discussion: Knowledge Creation and Social Justicementioning
confidence: 99%
“…In the South African tertiary educational context, there has been a move to decolonise knowledge. This has resulted in turbulence with many educators uncomfortable within the uncharted territory within which they work (Baron, 2017(Baron, , 2016a. Other challenges include new requirements for teaching such as ICT (information and communication technology) in the classrooms, additional assessments or even conflicts in the employment contract and so forth, also requires a level of adaptation.…”
Section: Openness and Adaptationmentioning
confidence: 99%